Guidance by the Attorney General for Northern Ireland pursuant to Section 8 of the Justice (Northern Ireland) Act 2004. Human Rights Guidance for the Police Service of Northern Ireland, the Public Prosecution Service, the Probation Board for Northern Ireland and the Northern Ireland Courts and Tribunals Service : Domestic Abuse and Stalking. No 13, (2018) - Northern Ireland., Office of the Attorney General,
No abstract available